EFEKTIVITAS PENGGUNAAN MODEL PEMBELAJARAN RECIPROCAL TERHADAP KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR SISWA PADA MATERI ENERGI MEKANIK - Ira Matialo; Marianus; Sixtus Iwan Umboh (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2023)
This study aims to determine the effectiveness of using the Reciprocal learning model on critical thinking skills and student learning outcomes. This research was conducted at SMA N 1 Likupang North Minahasa. In this study, the sample was taken using a total sampling technique with class X MIA II as the research sample in a one group pretest posttest design. The instrument in this study used cognitive description tests in the form of pre-test and post-test to measure student learning outcomes and non-tests in the form of observation sheets to observe students' critical thinking skills during learning. The results of the study were calculated using the paired sample t-test from the results of the pretest posttest sig <0.001 and the n-gain test with an n-gain score of 0.66 and an n-gain percent value of 66.92. Then the average value of the observations in the form of a percentage of the initial critical thinking ability of 0.88 is included in the less active category and the final critical thinking ability of 2.53 is included in the active category. And the results of this study concluded that H_a was accepted, meaning that the use of the Reciprocal learning model was effective in improving students' critical thinking skills and learning outcomes